Prevalensi Praktik Child Labor pada Usahatani Kopi di Kelompok Tani Bumi Rahayu, Kabupaten Trenggalek - Aditya Arief Rachmadhan; Intan Mega Maharani; Dita Rosyita; Putri Nurmalitasari; Ekamonika Manihuruk (Universitas Veteran Bangun Nusantara, 2026)
he sustainability of the coffee agribusiness is determined not only by economic and environmental dimensions but also by social sustainability, including the protection of children from child labor. This study aims to identify the forms and characteristics of children's involvement in coffee farming and to evaluate whether such involvement meets the child labor criteria established by the International Labour Organization (ILO). This study employed a descriptive-explanatory research design. Data were collected through questionnaires and interviews with six coffee farmers who were members of the Bumi Rahayu Farmer Group. The results revealed that the prevalence of child labor in coffee farming within the Bumi Rahayu Farmer Group was 16.67%, indicating a relatively low occurrence. Children's involvement was primarily intended to assist their parents, learn coffee cultivation practices, and compensate for family labor shortages, reflecting the concepts of child participation and children's work. Nevertheless, children were also involved in hazardous tasks and experienced disruptions to their educational activities. Based on the ILO criteria, these practices were therefore classified as child labor.